PENGARUH MOBILE BANKING, GAYA HIDUP DAN LITERASI KEUANGAN TERHADAP SIKAP TABZIR PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH BIMA - Wulan, Nur; Rasyad Al Fajar, Muhammad; Husniah, Dinah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to empirically test the influence of mobile banking, lifestyle and financial literacy on tabzir attitudes in students of Muhammadiyah University of Bima. This study uses an associative quantitative approach. A sample of 365 respondents was selected through purposive sampling technique from a population of 4,191 students. The results of the study indicate that mobile banking and lifestyle have a positive and significant effect on students' tabzir attitudes. Conversely, financial literacy has a negative but insignificant effect. Simultaneously, mobile banking, lifestyle and financial literacy have a significant effect on tabzir attitudes in students of Muhammadiyah University of Bima. This study contributes to Islamic economic literature by integrating the concept of tabzir in the perspective of the Qur'an with the theory of consumer behavior and digital finance. These findings recommend the need for structured financial education for students, especially in the use of mobile banking.